2011
DOI: 10.1592/phco.31.6.609
|View full text |Cite
|
Sign up to set email alerts
|

Continuous‐Infusion Neuromuscular Blocking Agents in Critically Ill Neonates and Children

Abstract: Neuromuscular blocking agents (NMBAs) are often administered as a prolonged (> 24 hrs) continuous infusion in infants and children in the intensive care unit for a variety of reasons including facilitation of oxygenation and ventilation. No guidelines on the use of NMBAs in pediatric patients are available yet in the United States; however, pediatric guidelines are available in the United Kingdom. Based on a 2007 U.S. survey, the most commonly used nondepolarizing NMBAs for sustained neuromuscular blockade in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Rationale: The most commonly described method to assess the level of neuromuscular blockade in critically ill patients receiving NMBAs is by peripheral nerve stimulation or TOF monitoring. One to three twitches typically indicates adequate neuromuscular blockade (178). Surveys have reported that TOF monitoring along with clinical assessment is used in 63–84% of critically ill patients receiving NMBAs (179, 180), whereas a small percentage of patients are assessed using only TOF (181).…”
Section: Resultsmentioning
confidence: 99%
“…Rationale: The most commonly described method to assess the level of neuromuscular blockade in critically ill patients receiving NMBAs is by peripheral nerve stimulation or TOF monitoring. One to three twitches typically indicates adequate neuromuscular blockade (178). Surveys have reported that TOF monitoring along with clinical assessment is used in 63–84% of critically ill patients receiving NMBAs (179, 180), whereas a small percentage of patients are assessed using only TOF (181).…”
Section: Resultsmentioning
confidence: 99%
“…Due to its metabolism via ester hydrolysis and Hoffman elimination, it may be a superior option for patients with renal or hepatic insufficiency requiring an NMBA, as the potential for drug accumulation is minimal in comparison with other agents. 11 Cisatracurium may be used more frequently during shortages of other NMBAs. Appropriate indications for NMBA infusions in an ICU setting include the management or facilitation of mechanical ventilation, treatment of muscle spasms, management of increases in intracranial pressure, and control of decreases in oxygen consumption when patients have failed other treatments.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the many non-depolarizing neuromuscular blockers used but has the distinct advantage of being fast-acting and reversible [ 21 ]. It is often used in critically ill, mechanically ventilated children when sedation alone is inadequate to achieve effective mechanical ventilation [ 22 ]. The occurrence of allergic or anaphylactic reactions is a known risk for rocuronium; its occurrence in children appears very rare as to date only three case reports have been published [ 23 ].…”
Section: Interventionsmentioning
confidence: 99%